The Satisfaction and Solutions Approach of Water Users for the Services Provided by the Water Supply State Enterprise in Luang Prabang Province (Case study: Luang Prabang City) - DUANGCHAMPA, kathi; INTHAPANYA , Sangkhom; CHANSAVANG , Bounsana (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The objectives of this study were: (1) to assess the level of satisfaction among water users with the services provided by the Water Supply State Enterprise of Luang Prabang City; and (2) to explore users' suggestions for improving these services. Data were collected using questionnaires administered to a sample of 390 households across 64 areas classified as type 1 residential water users within Luang Prabang City. The data were analyzed using the SPSS program. The results indicated that overall satisfaction with the services provided by the Water Supply State Enterprise—specifically in terms of water quality, billing and collection services, water pressure, repair services, and public relations—was moderate (Mean = 3.17, S.D. = 0.26). Regarding suggested improvements, users proposed enhancing water pressure, ensuring timely repair services, maintaining an adequate water supply during the dry season, and improving public communication and other related services. These proposed improvements accounted for 35.90% of the total recommendations.